2021
DOI: 10.1371/journal.pgen.1009195
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant regulation of a poison exon caused by a non-coding variant in a mouse model of Scn1a-associated epileptic encephalopathy

Abstract: Dravet syndrome (DS) is a developmental and epileptic encephalopathy that results from mutations in the Nav1.1 sodium channel encoded by SCN1A. Most known DS-causing mutations are in coding regions of SCN1A, but we recently identified several disease-associated SCN1A mutations in intron 20 that are within or near to a cryptic and evolutionarily conserved “poison” exon, 20N, whose inclusion is predicted to lead to transcript degradation. However, it is not clear how these intron 20 variants alter SCN1A expressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 51 publications
4
22
0
1
Order By: Relevance
“…An analysis of RNA-seq data of wild type mouse cortex revealed that throughout development, the inclusion of exon 20N decreases, accompanied by the increase in overall Scn1a mRNA levels. A similar pattern was observed for sodium channel, voltage-gated, type VIII, alpha ( Scn8a ) ( Voskobiynyk et al, 2021 ). Scn8a pre-mRNA contains two alternatively spliced exons, 18A and 18N.…”
Section: Aberrant Pe Regulation Is Implicated In Neurological Disorderssupporting
confidence: 72%
See 4 more Smart Citations
“…An analysis of RNA-seq data of wild type mouse cortex revealed that throughout development, the inclusion of exon 20N decreases, accompanied by the increase in overall Scn1a mRNA levels. A similar pattern was observed for sodium channel, voltage-gated, type VIII, alpha ( Scn8a ) ( Voskobiynyk et al, 2021 ). Scn8a pre-mRNA contains two alternatively spliced exons, 18A and 18N.…”
Section: Aberrant Pe Regulation Is Implicated In Neurological Disorderssupporting
confidence: 72%
“…Importantly, the pathogenic variants, all of which have intronic lesions, promote PE (exon 20N) inclusion leading to NMD of the SCN1A transcripts, thereby lowering expression levels of the sodium channel ( Carvill et al, 2018 ). In a different study, CRISPR/Cas9 was used to knock-in (KI) a pathogenic, PE promoting, variant of sodium channel, voltage-gated, type I, alpha ( Scn1a ) to generate a Dravet Syndrome (DS) mouse model ( Voskobiynyk et al, 2021 ). Scn1a +/KI mice exhibited decreased levels of Scn1a mRNA and protein in the brain, as well as an increase in exon 20N inclusion compared to control mice.…”
Section: Aberrant Pe Regulation Is Implicated In Neurological Disordersmentioning
confidence: 99%
See 3 more Smart Citations